2021
DOI: 10.21474/ijar01/13823
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening, Total Polyphenols and Flavonoids Content and Antiradical Activity of Methanolic Extract of Annickia Chlorantha From Gabon

Abstract: In traditional medicine, Annnickia chlorantha (Annonaceae)is used in many parts of Africa to treat several pathologies. It is used for the management of stomach problems, for the treatment of jaundice, tuberculosis, urinary tract infections, malaria, hepatitis and ulcers forms, for gallstones or even diarrhea. The phytochemical analysis and determination of the antiradical activity of the methanolic extract of the trunk bark from Annickia chlorantha from Gabon was the subject of this study. Phytochemical scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Pharmacological studies of some Lannea species have shown their anticancer, antibacterial and antioxidant activities (Sivaraj et al, 2018;Md. Hossain et al, 2018;Sabo et al, 2019;Mbaoji et al, 2020, Ombouma et al, 2022. The edible fruits of most of them are well known for their nutritional value in food or as a food supplement, and have enormous potential contribution in the economy and households (Atato et al, 2011;Sereme et al, 2014;Goudégnon et al, 2016;Diarra et al, 2016;Muhammad et al, 2018;Konaré et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological studies of some Lannea species have shown their anticancer, antibacterial and antioxidant activities (Sivaraj et al, 2018;Md. Hossain et al, 2018;Sabo et al, 2019;Mbaoji et al, 2020, Ombouma et al, 2022. The edible fruits of most of them are well known for their nutritional value in food or as a food supplement, and have enormous potential contribution in the economy and households (Atato et al, 2011;Sereme et al, 2014;Goudégnon et al, 2016;Diarra et al, 2016;Muhammad et al, 2018;Konaré et al, 2022).…”
Section: Introductionmentioning
confidence: 99%